C-Reactive Protein-to-Albumin Ratio: A Novel Inflammatory Marker and Disease Activity Sign in Early Rheumatoid Arthritis - Onder, Mustafa Erkut; Orucoglu, Nurdan; Omar, Firat; Canataroglu, Abdullah (Aktuelle Rheumatologie, 2021)
Objective A novel inflammation-based score, C-reactive protein (CRP)-to-albumin ratio (CAR), has been shown to have an association with the inflammatory status in several diseases. We aimed to analyse the association between CAR and disease activity in patients with early rheumatoid arthritis (RA) and to determine the cut-off value of CAR in early and established RA.Methods A total of 177 patients with RA and 111 age and gender-matched healthy controls were included in this study. Cases with a disease duration of less than 1 year were classified as early RA. Serum albumin, CRP, erythrocyte sedimentation rate (ESR), Disease Activity Score-28 (DAS-28-ESR), Clinical Disease Activity Index (CDAI) and Health Assessment Questionnaire (HAQ) scores were recorded.Results CAR was 2.44 (0.21–30.83) in the RA group and 0.45 (0.21–10.47) in the control group (p<0.001). Eighty-seven (49.15%) of the RA cases were classified as early RA. The analyses indicated that the ESR, CRP and CAR values were higher in patients with early RA than in those with established RA and controls. CAR was correlated with albumin, CRP, ESH, DAS-28 and HAQ scores in both early RA and established RA groups. The receiver operating characteristic curves revealed a CAR cut-off value of 2.67 (80% sensitivity and 85% specificity) and 1.63 (77% sensitivity and 72% specificity) for the prediction of early and established RA, respectively.Conclusion CAR, a formulated ratio, has been described as a predictor for disease activity in patients with early RA as well as in those with established RA. However, CAR has higher sensitivity and specificity for early RA than for established RA.Ziel der Arbeit Das C-reaktive Protein (CRP)-zu-Albumin-Verhältnis (CAR), ein neuartiger entzündungsbasierter Score, zeigte eine Korrelation mit dem Entzündungsstatus bei verschiedenen Krankheiten. Unser Ziel war es, die Assoziation zwischen CAR und Krankheitsaktivität bei Patienten mit früher rheumatoider Arthritis (RA) zu analysieren und den cut-off-Wert von CAR bei früher und etablierter RA zu bestimmen.Methoden Insgesamt wurden 177 Patienten mit RA zu 111 alters- und geschlechtsgematchten gesunden Personen in diese Studie aufgenommen. Fälle mit einer Krankheitsdauer von weniger als 1 Jahr wurden als frühe RA klassifiziert. Die Werte für Serumalbumin, CRP, Erythrozytensedimentationsrate (ESR), Disease Activity Score-28 (DAS-28-ESR), Clinical Disease Activity Index (CDAI) und Health Assessment Questionnaire (HAQ) wurden aufgezeichnet.Ergebnisse CAR war 2,44 (0,21–30,83) in der RA-Gruppe und 0,45 (0,21–10,47) in der Kontrollgruppe (p<0,001). Siebenundachtzig (49,15%) der RA-Fälle wurden als frühe RA klassifiziert. Die Analysen zeigten, dass die ESR-, CRP- und CAR-Werte der Patienten mit früher RA höher waren als die der Patienten mit etablierter RA und die der Kontrollpersonen. CAR korrelierte mit Albumin, CRP, ESH, DAS-28 und HAQ-Scores sowohl in den Gruppen mit früher RA als auch mit etablierter RA. Die Empfängerkennlinien ergaben einen cut-off-Wert für CAR von 2,67 (80% Sensitivität und 85% Spezifität) und von 1,63 (77% Sensitivität und 72% Spezifität) für die Vorhersage einer frühen bzw. etablierten RA.Schlussfolgerung CAR, ein formulierter Quotient, wird als Vorhersagewert für die Krankheitsaktivität sowohl bei Patienten mit früher RA als auch bei Patienten mit etablierter RA beschrieben. CAR hat jedoch eine höhere Sensitivität und Spezifität für frühe RA als für etablierte RA.
Keywords: C-reactive protein; albumin; inflammation; rheumatoid arthritis